RELATIONSHIP OF LEI0234 MARKER WITH SOME PRODUCTIVE TRAITS OF LOCAL CHICKENS - H. D. Abdel karim,; A. A. Noori, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study utilized 100 local Iraqi laying hens, aged 67 days, which were individually housed in numbered cages (1 to 100) for the duration of the experiment, conducted from October 26, 2021, to March 5, 2022. The results revealed highly significant differences (P ≤ 0.01) in the number and frequency of the LEI0234 marker among the different alleles, with the A1 allele showing superior performance compared to the other alleles. The A1 allele appeared in various genotypic forms, with a frequency of 27.00%. No significant differences were observed among the alleles in terms of body weight, age at sexual maturity, egg mass, or feed conversion efficiency. However, significant differences (P ≤ 0.05) were recorded during the 84-day period. Egg weight showed significant differences (P ≤ 0.05) during the production periods of 14 and 28 days. However, no significant differences were observed during the subsequent periods of 42, 56, 70, 84, 98, and 100 days. In contrast, feed consumption exhibited significant differences (P ≤ 0.05) during the production periods of 14, 28, 42, 56, 98, and 100 days.